2014
DOI: 10.4103/2229-5178.142491
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of syphilis among street-based female sex workers in Nanchang, China

Abstract: Background:Female sex workers (FSWs) play a critical role in the heterosexual transmission of human immunodeficiency virus (HIV)/sexually transmitted infections (STIs) in China. Several studies reported that street-based FSWs have higher risk behaviors than establishment-based FSWs. Therefore, street-based FSWs should be specifically targeted for HIV and STIs intervention programs.Objectives:This study aims to investigate the prevalence rates and risk factors of HIV and syphilis among FSWs in Nanchang, China.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
(58 reference statements)
2
8
0
Order By: Relevance
“…We found that FSWs who used drugs were at higher risk of HIV acquisition than those who did not, which was also shown in another study in Vietnam [ 26 ]. We also found that FSWs who always used condoms with clients in the previous month were negatively associated with new HIV infection, which has also been recognized in many other studies [ 27 29 ]. The above factors indicate that FSWs who were LTFU in the Kaiyuan cohort had a lower risk of acquiring HIV.…”
Section: Discussionsupporting
confidence: 86%
“…We found that FSWs who used drugs were at higher risk of HIV acquisition than those who did not, which was also shown in another study in Vietnam [ 26 ]. We also found that FSWs who always used condoms with clients in the previous month were negatively associated with new HIV infection, which has also been recognized in many other studies [ 27 29 ]. The above factors indicate that FSWs who were LTFU in the Kaiyuan cohort had a lower risk of acquiring HIV.…”
Section: Discussionsupporting
confidence: 86%
“…Secondly, after retirement, older males were likely to engage in commercial sexual activities [19], which led to the rise of HIV/syphilis prevalence in the population of China’s older males [7, 35]. A high rate of inconsistent condom use at commercial sex was reported in several studies [3638], and those with inconsistent condom use at commercial sex had a higher risk of the HIV/syphilis infection than those with consistent condom use [36, 39]. Besides, selling sex was identified as a risk factor of the HIV/syphilis infection because of the high frequency of unprotected anal intercourse and multiple sexual partners [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…STDs. This research shows that syphilis infection rate of OFSWs in Qingdao is lower than which is in Sichuan Province(62.5%) [6] . But it is higher than prevalence rate of young female sexual workers(7.36) ,…”
mentioning
confidence: 59%
“…But that doesn't mean the OFSWs without infection but means infection rate is still low. Due to the infection with syphilis and other sexually transmitted diseases, genital tract mucosal ulcer will appear and the susceptibility of HIV will increase [17] ,also OFSWs with syphilis and other venereal diseases will develop colossal ulcer in genital tract which increases the susceptibility of HIV. STDs is an important co-factor infected with the HIV [18] .…”
Section: Object Of Studymentioning
confidence: 99%